2020
DOI: 10.1002/pa.2545
|View full text |Cite
|
Sign up to set email alerts
|

Remittances and financial development in Africa

Abstract: Despite the magnitude of remittances as an alternative source of investment financing in Africa, the financial sector in Africa has significantly remained underdeveloped and unstable. Finding a solution to Africa's financial deregulation problems has proved tenacious partly because of inadequate literature that explain the nature of Africa capital and financial markets which has shown to be unorganised, spatially fragmented, highly segmented and invariably externally dependent. We examine the structural linkag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 67 publications
(109 reference statements)
1
11
1
Order By: Relevance
“…Donou-Adonsou et al (2020), from the results of panel cointegration and Autoregressive Distributed Lag (ARDL) PMG regression, reported a long-run positive and significant impact of remittances on the financial development of top remittance-receiving countries in Sub-Saharan Africa. Using the same method, Adekunle et al (2020) reported similar findings for a panel of 53 African countries. Basnet et al (2020), based on the results of panel cointegration and PMG estimation, documented a positive impact of remittances on the financial development of South Asian countries.…”
Section: Introductionmentioning
confidence: 59%
“…Donou-Adonsou et al (2020), from the results of panel cointegration and Autoregressive Distributed Lag (ARDL) PMG regression, reported a long-run positive and significant impact of remittances on the financial development of top remittance-receiving countries in Sub-Saharan Africa. Using the same method, Adekunle et al (2020) reported similar findings for a panel of 53 African countries. Basnet et al (2020), based on the results of panel cointegration and PMG estimation, documented a positive impact of remittances on the financial development of South Asian countries.…”
Section: Introductionmentioning
confidence: 59%
“…Remittances were measured using net remittance inflows to recipient countries as used in the work of Adekunle et al (2020); labour was measured using labour participation rate as in Erten and Metzger (2019); the capital stock was proxied using gross fixed capital formation as in Topcu, Altinoz and Aslan (2020); the exchange rate was measured using the nominal exchange rate as used in Oseni, Adekunle and Alabi, (2019); inflation was measured using the GDP price deflator as in Galí and Gertler (1999); technology was measured using account ownership with a financial institution or mobile money service provider as used in Asongu (2013); the population was measured using total population as in Kibirige (1997). In Table 2, the description of the variables, their sources and motivating studies are presented for ease of understanding and flow.…”
Section: Methodsmentioning
confidence: 99%
“…To gauge the future of African economies within a remittance inflow–financial development relations, this paper follows the dual gap theoretical model as in Aggarwal et al (2011) and Adekunle et al (2020). The dual gap theory argues that developing countries smoothen the intertemporal constraints in their saving–investment gap using external financing options.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations